Corrosion and protection of metals in the rural atmosphere of "El Pardo", Spain (PATINA/CYTED project) (2003)
ABSTRACT: Atmospheric corrosion tests of metallic and organic coatings on steel, zinc and aluminium have been conducted in "El Pardo" (Spain) as part of the PATINA/CYTED project "Anticorrosive Protection of Metals in the Atmosphere". This is a rural atmosphere with the following ISO corrosivity categories: C2 (Fe), C2 (Zn), C3 (Cu) and CI (Al). Its average temperature and relative humidity is 13 °C and 62.8 %, respectively, and it has low SO2 and C r contents. Results of 42 months exposure are discussed. Atmospheric exposure tests were carried out for the following types of coatings: conventional paint coatings for steel and hot-dip galvanized steel (group 1), new painting technologies for steel and galvanized steel (group 2), zinc-base metallic coatings (group 3), aluminium-base metallic coatings (group 4), coatings on aluminium (group 5) and coil-coatings on steel, hot-dip galvanized steel and 55 % Al-Zn coated steel (group 6).